2015
DOI: 10.1515/foli-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Profitability Ratios and Company Size on Profitability and Investment Risk in the Capital Market

Abstract: A study was conducted of 15 food companies listed on the Warsaw Stock Exchange. The profitability of companies was measured by: return on assets (ROA), return on equity (ROE) and return on sales (ROS). Investment risk was measured by standard deviation and semi-deviation. The main objective of the study was to examine whether the average level and variability of selected indicators of profitability are reflected in the average level and the variability of returns on the capital market. An additional aim was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…This paper is an extension of research previously presented by Rutkowska--Ziarko (2015), which concluded that the total risk, defined as variability and semi-variability of the stock prices, is affected by the changeability of profit earned by the company. The aim of this paper is to propose a method for calculating downside accounting betas.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…This paper is an extension of research previously presented by Rutkowska--Ziarko (2015), which concluded that the total risk, defined as variability and semi-variability of the stock prices, is affected by the changeability of profit earned by the company. The aim of this paper is to propose a method for calculating downside accounting betas.…”
Section: Introductionmentioning
confidence: 67%
“…One of the solutions is to use the average level of a financial ratio in each sector as the target point. The same approach has been proposed for calculating semivariance of profitability ratios in work by Rutkowska-Ziarko (2015).…”
Section: Market Beta Accounting Beta and Downside Riskmentioning
confidence: 99%
“…R-square is the highest for mean ROE, it equals 23% for individual securities and 59% for the portfolio. In prior studies, a positive correlation between the profitability ratios and the quarterly average rates of return was observed for Polish food and con-Pobrane z czasopisma Annales H -Oeconomia http://oeconomia.annales.umcs.pl Data: 03/11/2020 06:44:36 U M C S struction companies (Rutkowska-Ziarko, 2015;Rutkowska-Ziarko & Pyke, 2018). Konchitichi, Luo, Ma, and Wu (2016) found a negative risk premium for ROA and positive risk premium for .…”
Section: 416mentioning
confidence: 93%
“…For this reason, profitability analysis is very important for the company and becomes the concern of shareholders who invest in the company. Company profitability can be measured by determining financial profitability ratios (Rutkowska-Ziarko, 2018). The improvement in profits due to the high profitability ratio of a company can attract investors and increase the company's stock price (Satryo et al, 2017).…”
Section: Profitabilitymentioning
confidence: 99%